Service quality assessment of the Quezon City Public Library from one perspective of its users - Cariaga, Esther C.; Dela Torre, Nathalie N. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2010)
Public libraries are information centers that are free for all. It accommodates everyone in whichever community it is in. It helps the community in continuous education of the people. For these, a public library should provide quality services to its clients. The study aimed to find out if the Quezon City Public Library meets its users' need through SERVQUAL. SERVQUAL is an evaluation instrument that measures the service quality of different institutions such as the library. In order to determine the service quality of an institution, it relates the expectation and perception of service quality with the use of gap analysis. A modified SERVQUAL questionnaire was developed to answer the objectives of the study.
Based on the survey conducted, the Quezon City Public Library did not generally meet the needs of their users. The library provided well enough for the basic needs inside the library such as lighting. However, significant problem in the collection was observed. Also, there are only five dimensions that reflect service quality in Quezon City Public Library. These are: Adequacy and Comprehensiveness, Assurance and Empathy, Responsiveness, Library as Place, and Self-sufficiency/Self-reliance. The respondents perceived the factor Library as Place to be the least important while the factor Adequacy and Ease of Access was perceived to be the most important. The respondents fairly rated all of the SERVQUAL dimensions, thus all dimensions passed the test of tolerance of the users of the Quezon City Public Library. "
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Quezon City Public Library -- Evaluation; Public libraries -- Philippines -- Quezon City